Nanocellulose as a Novel Cryoprotectant to Improve the Quality of Frozen Sour Cherries - Gençdağ, Esra; Görgüç, Ahmet; Yılmaz, Fatih Mehmet (Food and bioprocess technology, 2024)
Recent studies suggest that nanocelluloses may help protect frozen foods’ structure, thereby preserving quality parameters during storage. This study examined the impact of nanocellulose treatment on the frozen quality of sour cherries. Nanocellulose produced from pistachio hull was incorporated into sour cherries using vacuum impregnation, and its cryoprotective role was assessed using three different freezing techniques: static, air-blast, and individual quick frozen (IQF). Multivariate analysis of variance (MANOVA) demonstrated the interactive effects of the parameters. During 6 months of storage, nanocellulose pretreatment resulted in significantly lower drip loss, ion leakage, and color difference while retaining high levels of anthocyanin content and antioxidant capacity compared to the non-treated group. Texture analysis also showed that using nanocellulose could compensate for the disadvantage of slow freezing. Pectin methylesterase (PME) activity values fitted to 2nd order kinetic, and the highest residuals were determined in static freezing. Strong correlations ( P < 0.01) were found between drip loss and color difference ( r = 0.662), hardness and ion leakage ( r = 0.605), and color difference and a w values ( r = 0.628). Graphical Abstract